New Energetic Complex of Copper(II) Dinitramide Based Nitrogen‐rich Ligand Aminoguanidine(CH6N4): Synthesis, Structural and Energetic Properties. Issue 7 (15th May 2019) - Nosratzadegan, Keyvan; Mahdavi, Mohammad; Ghani, Kamal; Barati, Kazem
Abstract: The crystal structure of the energetic complex bis(aminoguanidine)copper(II) dinitramide [Cu(AG)2 ][DN]2 (I ), has been determined at 298 K using single‐crystal X‐ray diffraction technique. The Cu(II) atom is four‐coordinated by two imine N atoms and two amine N atoms from two aminoguanidine ligands, forming a slightly distorted square‐planar coordination. In the crystal structure, molecules are linked through intermolecular N−H…O hydrogen bonds, forming a network. The infrared spectrum showed a sharp peaks at 1650 and 1010 cm −1 which are typical of the conjugated C=N stretching due to the coordination of the imine nitrogen and NNN stretching dinitramide counterion, respectively. The thermal decomposition process of this complex was investigated through differential scanning calorimetry (DSC) and the sensitivities toward impact and friction were assessed using a BAM drophammer and a BAM friction tester. In the measurement ofI a violent explosion appeared destroying the setup. This may be a reason, due to the copper complex (I ), which crystallizes water free. The power of powder and single crystal ofI was measured by the Trauzl test are 425 and 427 cm −3 for 10 gI (142 % TNT and 88 % RDX). Abstract :